The proteomics of wool fibre morphogenesis - Plowman, Jeffrey E.; Harland, Duane P.; Ganeshan, Sivasangary; Woods, Joy L.; van Shaijik, Bede; Deb-Choudhury, Santanu; Thomas, Ancy; Clerens, Stefan; Scobie, David R. (Journal of structural biology, 2015)
Gel and gel-free proteomic techniques have been used for the first time to directly study the proteins present in whole wool follicles and dissected portions of follicles that correlated with morphological changes in the developing fibre as determined by transmission electron microscopy. Individual wool follicles were dissected into four portions designated as the bulb, elongation, keratogenous and keratinisation portions. Gel-free proteomic analysis of dissected portions from 30 follicles showed that the first keratins to appear were K31, K35 and K85, in the bulb portion. The first epithelial KAP, trichohyalin, was detected in the bulb portion and the first cortical KAP, KAP11.1 was found in the elongation portion. Other major trichocyte keratins and cortical KAPs began to appear further up the follicle in the keratogenous and keratinisation zones. These results were consistent with what has been observed from gene expression studies and correlated well with the morphological changes observed in the follicle. Other proteins detected by this approach included the keratin anchor protein desmoplakin, as well as vimentin and epithelial keratins, histones, ribosomal proteins and collagens. Two-dimensional electrophoretic (2DE) analysis of dissected portions of 50 follicles revealed substantial changes in the position, number and intensity of the spots of the trichocyte keratins as they progressed through the follicle zones, suggesting that they are subject to modification as a result of the keratinisation process. Also present in the 2DE maps were a number of epithelial keratins, presumably from the inner and outer root sheaths, and the dermal components.